Cancel Culture di Era Media Baru: Analisis Komunikasi Atas Implikasi Sosial dalam Kasus Overclaim Skincare - Djamzuri, Muhammad Irfan; Mulyana, Agung Putra (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The cancel culture phenomenon that can be found in digital society is that individuals such as public figures, groups or brands can be exposed to social exclusion, criticism and even massive boycotts on social media. A phenomenon often found on platforms  Cancel culture occurs due to the composition of the rapid dissemination of information and the influence of developing public opinion plus algorithms that apply it until content goes viral on social media. In this digital era of connectivity, local phenomena can become global issues, the Cancel culture effect is a consequence that cannot be avoided by individuals or groups and a company brand.  Research with communication, social, cultural and psychological approaches, as well as duality analysis of Cancel cultural phenomena as social control or giving rise to injustice and freedom of expression. The literature study approach allowed Cancel culture to be found in several cases in Indonesia, especially involving health figures such as Dr. Richard Lee and detective doctor content on TikTok, as well as raising the issue of overclaimed Skincare products and Skincare products that are thought to be dangerous.  The concept of "canceling" in Cancel culture is a social media phenomenon that has emerged regarding Skincare which is suspected of being overclaimed and dangerous Skincare which is considered to violate norms or is inappropriate by the general and digital public. This phenomenon contributes to opinions and opinions in the form of hashtags and triggers the emergence of the phenomenon of conformity and spiral of silence in society which can pave the way for further research.